Case report: Fatal ischemic stroke induced by unruptured traumatic intracranial vertebral artery dissection - Wen, Shuheng; Unuma, Kana; Inaji, Motoki; Makino, Yohsuke; Nagano, Shutaro; Harada, Kazuki; Arai, Nobutaka; Uemura, Koichi (Frontiers in Neurology, 2023)
Intracranial vertebral artery dissection (IVAD) is rare and potentially fatal due to the risk of secondary subarachnoid hemorrhage once ruptured. Unruptured traumatic IVAD is even rarer and can result in ischemic stroke, yet mostly benign when timely diagnosed. Herein, we present an uncommon case of a patient who underwent a fatal ischemic stroke induced by unruptured traumatic IVAD. The patient was symptomatic soon after being physically assaulted but left untreated until acute deterioration for multiple brain infarctions occurred, secondary to IVAD-induced cerebellar stroke. Fifteen days later, he died, regardless of an urgently performed thrombectomy. Multiple serial histologic examinations revealed an unruptured dissection of the intracranial vertebral artery with a slit-like tear of the intimal and medial layers, considered to be the culprit lesion. The 15-day prolonged onset of stroke was rare in traumatic IVADs. Furthermore, the slit-like tear of the intimal layer in our case may support the initial intimal laceration hypothesis for VAD pathogenetic mechanism. Since limited pathohistological information is available regarding ischemic IVAD, we believe this rare case will be beneficial in understanding the pathophysiology of ischemic IVAD.